Pengaruh Edukasi Pernikahan Dini Menggunakan eBook “Remaja dan Pernikahan Dini” di MA Malaka Lombok Utara Nusa Tenggara Barat Tahun 2025 - Eka Rudy Purwana; Ridawati Sulaiman; Chandra Irawan; Hadi Kusuma Atmaja; Taufiqurrahman (Bima Nursing Journal, 2025)
Early marriage remains a critical issue affecting adolescent health and development globally, including in Indonesia. Lack of information is a contributing factor to the high prevalence of early marriage. This study aims to analyze the effect of health education using an E-book on adolescents' knowledge regarding early marriage at MA Malaka. This research utilized a quantitative pre-experimental design with a One Group Pre-Post Test approach. The study was conducted from May to June 2025 with a population of 62 students. The sampling technique used was total sampling, resulting in a sample size of 62 respondents. Data were collected using a knowledge questionnaire and analyzed using the Wilcoxon Signed Ranks Test. The results showed that before the intervention, the majority of respondents had sufficient knowledge (50%) with a mean score of 5.65. After the E-book intervention, the majority of respondents had good knowledge (60%) with an increased mean score of 7.44. The statistical analysis revealed a p-value of 0.000 (< 0.05). In conclusion, there is a significant effect of education using the "Remaja dan Pernikahan Dini" E-book on increasing adolescents' knowledge about early marriage. This media is recommended as an effective educational tool for schools. Keywords: Adolescent, E-book, Early Marriage, Knowledge